Atmospheric mercury emissions from two pre-calciner cement plants in Southwest China. (15th February 2019) - Li, Xinyu; Li, Zhonggen; Wu, Tingting; Chen, Ji; Fu, Chengcheng; Zhang, Leiming; Feng, Xinbin; Fu, Xuewu; Tang, Li; Wang, Zhikang; Wang, Zhibo
Abstract: China produces the most cement product worldwide, and cement plants (CPs) have been regarded as the largest anthropogenic sources of atmospheric mercury (Hg) emissions in China since 2009. Onsite studies of this source are scarce compare to the huge numbers of CPs in China. Hence, quantifying Hg emissions from more CPs is needed in reducing the large uncertainties existed in the current Hg emission inventories and for assessing subsequent impacts of Hg on human and ecosystem health. In this study, two pre-calciner CPs in Guizhou province of Southwest China were selected for quantifying the emission factor and mass balance of Hg. Results showed that Hg emission levels in the two CPs were obviously different due to the differences in Hg input and circulation in the production system. In cement plant #1 (CP #1), the input and output of Hg reached a dynamic equilibrium condition, the emission factor was 76.1 mg Hg·t −1 clinker, and Hg concentration in the stack flue gas was in the range of 14.46–16.64 μg m −3 . In cement plant #2 (CP #2), Hg was in an enriching status because it was a new plant with operation of several months and most input Hg was retained inside the production system, hence with a much lower emission factor of 1.8 mg Hg·t −1 clinker and Hg concentration of 0.15–0.49 μg m −3 in the stack gas. Kiln tail stack was the main output pathway of Hg in the clinker production process. With removal efficiency of 73.06% and 99.95% at kiln tail by ESP in CP #1 and humidifier + ESP-FF in CP #2, respectively, Hg emitted into the atmosphere was mainly in the forms of gaseous oxidized mercury (Hg 2+ ) and gaseous elemental mercury (Hg 0 ). Besides, the operation mode (on or off) of raw mill had great impact on the concentration and speciation of Hg in flue gas and flue gas temperature at kiln tail. In the clinker production system, limestone is the main source of Hg input (41.4–56.4%), followed by the fueled coal (15.3–32.5%). While, in the clinker to cement production process, the additives (mainly gypsum from coal-fired power plants, 83.2–94.4%) was the main source of Hg in the cement because Hg concentration in the clinker was very low. Graphical abstract: Highlights: Mercury emission levels from two cement plants are contrasting. Hg input and circulation determined the atmospheric emission levels. Short term (several months) operation result in most Hg retained inside the production system. Operation mode (on or off) of raw mill at kiln tail has obvious impact on Hg concentration and speciation.